E-BANKING – A SUSTAINABLE DEVELOPMENT IN BANKS - S. , Manjushree (International Journal For Research In Business, Management And Accounting, 2020)
Indian banks have leveraged technology and introduced innovative banking product and services to attract and retain the customer for sustainable development in Banks. E-banking is the automated delivery of new and traditional banking products, services directly to the customers through electronic, interactive communication channels, while E-banking services bring down the cost per transaction, increase efficiency by reducing workload of staff, they help to increase accuracy , speed, save time, money and effort of customers. Thus E banking services impacts the customer services and leads to better customer satisfaction. They enable the bank to transact more business by offering various services in cost effective way on one side and to get more customer satisfaction on the other. To analyze the relationship between demographic variable and perception towards e banking services, a structured questionnaire used to collect the data from a random sample of 50 customers from State bank of Mysore in Bhadravathi, Percentage analysis and chi square test are applied for data analysis and interpretation. Finally, it attempts to offer suitable suggestions and conclusions to enhance the awareness of E-banking services.